The influence of ethylene, gibberellins and brassinosteroids on energy and nitrogen-fixation metabolites in nodule tissue - McGuiness, Peter N (Plant science : an international journal of experimental plant biology, 2021)
Crown Copyright © 2021. Published by Elsevier B.V. All rights reserved.